Between Borders and Bombs: The Existence and Resistance of the Sahrawi Territory through the Bodies of Sahrawi Women - Ysunza, Valeria (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
This article analyses the Sahrawi territory and the resistance of its people based on a critical feminist geography approach. The main purpose of the research is to conceive the bodies of Sahrawi women which actively participate in the construction of their territory (not recognised after the invasion of Morocco and Mauritania in 1975) as territories in conflict and in constant risk, emphasising the power relationship between body and territory as spatial scales. The article uses dance as a tool for an ethnographic approach and explores the importance of "artivism" as a political act and as a methodology of action-participation in the Artifariti Festival. We participated in this festival as part of the Hanin Performing Dance Collective in order to understand and learn directly about the situation in which Sahrawi women live. Spaces for reflection and resistance arise and alternatives for and with the Sahrawi people are generated through art.